"Invest Time in Learning the Technology of Your Customers and Not Just Your Own": Some words of wisdom for the next generation of CTOs from Eagleyard's Dirk Schumann. Issue 5 (9th October 2019) - Pozo, Jose
Abstract: In this interview, Jose Pozo, EPIC's CTO talks to Dr Dirk Schumann, formerly a production manager for BMW and now CTO of Eagleyard Photonics.